Influence of Inflation and Tax on Business Development in the Brother Store Dili, Timor-Leste - Silva, Jose da; Daci, Romeu Marques; Silva, Alegandria Da (Yayasan Sinergi Kawula Muda, 2024)
This study aims to analyze the effect of inflation and taxes on business development at Brother Store Dili, Timor-Leste. This research was conducted at Maun Alin Dili, Timor-Leste with the topic Influence and Taxes on Business Development at Brother Store Dili, Timor-Leste. The reason for taking this topic is that the researcher sees the existing problems, these problems are Inflation and Taxes on Business Development. This study used quantitative methods and used data analysis techniques, namely multiple linear regression with the formula Y = a + b1x1 + b2x2 + e. The results of the Hypothesis Test T (H1) Inflation (X1) on Business Development (Y) from the SPSS output show, for the table above it can be seen that the value of the independent variable Inflation (X1) with a level of - With a confidence level of 95%. Based on the above findings it can be concluded that: Thitung <= Table, then Ho or null hypothesis is accepted and Ha (alternative technique) is not accepted, meaning that there is no influence and significant relationship between Inflation (X1) on Business Development Hypothesis Test Results (Y).T (H2) Tax (X2) on Business Development (Y) from the results of the SPSS output, for the table above it can be seen that the Thitung value of the independent variable Tax (X2) is 6.964> and the Table value is 1.694. Thitung> Table with a significance level of 0.000 or 0.0% lower than the error rate of 0.05 or 5%. With a confidence level of 95%